2023
DOI: 10.3892/ijo.2023.5522
|View full text |Cite
|
Sign up to set email alerts
|

New insights into lipid metabolism and prostate cancer (Review)

Abstract: Prostate cancer (PCa) is the most common malignant tumor of the male urological system and poses a severe threat to the survival of middle-aged and elderly males worldwide. The development and progression of PCa are affected by a variety of biological processes, including proliferation, apoptosis, migration, invasion and the maintenance of membrane homeostasis of PCa cells. The present review summarizes recent research advances in lipid (fatty acid, cholesterol and phospholipid) metabolic pathways in PCa. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 165 publications
0
1
0
Order By: Relevance
“…Alternatively, several studies show that prostate cancer cells and PC-3 cells, in particular, show different lipid profiles [ 49 , 50 ]. Moreover, in a previous study, we showed that the membrane and cell viscosity of PC-3 were different from those of the non-tumor control [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, several studies show that prostate cancer cells and PC-3 cells, in particular, show different lipid profiles [ 49 , 50 ]. Moreover, in a previous study, we showed that the membrane and cell viscosity of PC-3 were different from those of the non-tumor control [ 22 ].…”
Section: Discussionmentioning
confidence: 99%